2005
DOI: 10.1177/0969776405048496
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization for Turkey

Abstract: During the last quarter of the last century, particularly in the developed countries, we witnessed an extraordinary change in how capital organizes and reproduces itself, which had and still has profound effects on other parts of the world. Economic restructuring and globalization became slogans of a post-Fordist era among scholars from various strands and disciplines (Dicken

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 65 publications
0
4
0
1
Order By: Relevance
“…However, our brief experience with RDAs has revealed that the practices of RDAs are largely uniform (Yavan et al, 2022). According to us, recent stagnation in Turkey’s negotiations to join the EU and the trend toward centralized governance have contributed much to this one‐size‐fits‐all trend, as stated by Dulupçu (2005), in regional development in Turkey. In this regard, it would be beneficial to reorganize the structure of RDAs to align with a bottom‐up approach to regional development policy.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, our brief experience with RDAs has revealed that the practices of RDAs are largely uniform (Yavan et al, 2022). According to us, recent stagnation in Turkey’s negotiations to join the EU and the trend toward centralized governance have contributed much to this one‐size‐fits‐all trend, as stated by Dulupçu (2005), in regional development in Turkey. In this regard, it would be beneficial to reorganize the structure of RDAs to align with a bottom‐up approach to regional development policy.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Daha az gelişmiş bölgelerin yetersiz beşeri sermaye ve inovasyon altyapısı nedeniyle yeterince fayda sağlayamaması, gelişmiş ve geri kalmış bölgeler arasındaki ekonomik açığın daha da artmasına neden olabilmektedir. Gezici ve Hewings (2004), Dulupçu (2005), Celebioglu ve Dall'Erba (2010) ve Karahasan, Doğruel ve Doğruel (2016) tarafından da ifade edildiği gibi Türkiye, uzun yıllardır doğu ve batı arası bölgesel eşitsizlikler problemiyle baş etmeye çalışmaktadır. Bu husus göz önüne alındığında, Türkiye için ilişkili ve ilişkisiz çeşitlilik ve gelir dağılımı arasındaki ilişkilerin ortaya çıkarılması önemli bir araştırma konusu olarak ortaya çıkmaktadır.…”
Section: Introductionunclassified
“…This situation may lead to an increase in the economic gap between the developed and less developed regions. As stated by Gezici and Hewings (2004), Dulupçu (2005), Celebioglu and Dall'Erba (2010), and Karahasan, Doğruel, and Doğruel (2016), Turkey has been trying to cope with the regional inequalities between east and west parts of the country for many years. For this reason, revealing the relationships between related and unrelated variety and income distribution for Turkey emerges as an important research topic.…”
Section: Introductionmentioning
confidence: 99%
“…These problems, such as the insufficiency of economic resources and human resources are at the | 84 local level: the low level of social capital in the regions 62 ; the lack or partial experience of local governance 63 ; and mistrust among actors and/or institutions involved in the governance process 64 . Here, one of the critical issues is to mediate overlapping local agendas among the stakeholders.…”
mentioning
confidence: 99%
“…During the very creation of RDAs, neither the Ministry of Development nor the State Institute of Statistics consulted with any local/regional stakeholders on the design of the regional setting 56 . The selection of the provinces to host the RDAs was not clear and the process was not sufficiently transparent 57 .…”
mentioning
confidence: 99%